Tell Us a Story Granddad: Age and Origin of an Iconic Australian Lungfish - Mayne, Benjamin; Espinoza, Tom; Roberts, David (Frontiers in Environmental Science, 2022)
The modern discovery of the Australian lungfish (Neoceratodus forsteri) by European settlers in 1870 was considered one of the most important events in natural history by leading international scientists and naturalists of that time. Its distinct evolutionary lineage and unique extant morphological characteristics fostered the romantic zoological moniker ‘living fossil’. Although N. forsteri were suspected of being long-lived, a reliable estimate of maximum age has remained elusive. Maximum age is critical to inform wildlife management and conservation efforts, including the use of population viability models. To estimate the maximum age for N. forsteri, we sourced DNA from ‘Granddad’, the presumed longest-living lungfish known in a zoological park and utilised an epigenetic ageing clock developed for N. forsteri. This lungfish specimen was gifted to the Chicago John G. Shedd Aquarium from Australia in 1933 and lived there for 84 years until death in 2017. We estimated the age of Granddad at death to be 109 years (±6 years), confirming N. forsteri as a true centenarian species. Genotyping also revealed the natal origin of Granddad to be the Burnett River, Queensland, Australia, the location of the species’ original discovery in 1870. We demonstrate the application of novel molecular techniques to a unique long-lived and captive-raised specimen, to improve estimates of maximum age for the species, and to identify natal origin. This information will support future conservation efforts for this iconic yet endangered species.